Determinant Variables of Quality Management Practices in Micro and Small Enterprises in Ecuador - Pérez-Campdesuñer, Reyner (2023)
There is no consensus on whether quality management can always be developed with the same mechanisms, regardless of the size of the companies. Investigations in various latitudes have been motivated to lead to a conclusion in this regard, among other reasons for the great diversity of classification criteria of companies according to their size. This investigation aims to characterize the extent to which the quality management practices of micro and small enterprises in Ecuador differ from the practices of this discipline in medium and large enterprises. For this, information on the way in which the activity is developed in 992 organizations of the population under study was used and the degree of presence of determining variables in quality management was characterized. Among other results, the existence of significant differences in quality management depending on the size of the companies was found.